Primary Graft Dysfunction and Mortality Following Lung Transplantation: A Role for Proadrenomedullin Plasma Levels. Issue 2 (13th October 2015) - Riera, J.; Senna, A.; Cubero, M.; Roman, A.; Rello, J.; Study Group Investigators, the Vall d'Hebron Lung Transplant
Abstract : Primary graft dysfunction (PGD) after lung transplantation (LT) is a heterogeneous syndrome that comprises clinical presentations with diverse grades of severity. Proadrenomedullin (proADM) levels may be associated with PGD and may enhance its relationship with outcomes. We prospectively included 100 LT recipients. Plasma levels of proADM were measured at 24, 48 and 72 h after admission to the intensive care unit (ICU). We assessed their relationship with PGD grade and ICU mortality. Fifty patients (50%) presented grade 3 PGD at ICU admission. Twenty‐two patients (22%) developed grade 3 PGD at 72 h, the only grade associated with higher mortality (odds ratio 6.84, 95% confidence interval [CI] 1.47–38.44). ProADM levels measured at 24 h (3.25 vs. 1.61 nmol/L; p = 0.016) and 72 h (2.17 vs. 1.35 nmol/L; p = 0.011) were higher in these patients than the rest of the population. When we added the individual predictive utility of grade 3 PGD at 72 h for ICU mortality (area under the curve [AUC] 0.72, 95% CI 0.53–0.90) to that of ProADM at 72 h, the predictive value of the model improved (AUC 0.81, 95% CI 0.65–0.97). Higher levels of proADM measured following LT are associated with grade 3 PGD at 72 h. ProADM enhances the association of this entity with mortality.